Humor, skets en gemoedelikheid in verskillende stylfigure by Johannes Calvyn - Potgieter, P. C. (Faculty of Theology, University of the Free State, 2016)
A fairly general perception of John Calvin is that of a gloomy and even cheerless person. In many publications on his life and on his outlook on life, in particular, there is frequently nothing or hardly anything to be found on his humour and bonhomie. The author argues that there are many indications in his writings that show another side of this remarkable man. It is obvious that his contemporary colleagues often found him in a jovial mood, while his writings were certainly not without humour and even jest. It must be borne in mind that the humour of every period in history has its own kind of character. One should not necessarily view sixteenthcentury humour in terms of the twenty-first-century views. In a lighter mood, Calvin frequently expressed himself in various figures of speech, particularly metaphor and irony, which often have a hint of sarcasm.
Humour, jest and bonhomie in various figures of speech in John Calvin
Keywords: Calvin; Humour; Bonhomie; Figures of speech